Epidemiology of S. Pneumoniae-associated Pneumonias and the Analysis of Effectiveness of Vaccination against Pneumococcal Infection in Children under the Age of Six - A. V. Somova; V. V. Romanenko; A. A. Golubkova (Эпидемиология и вакцинопрофилактика)
Pneumococcal infection is one of the main causes of acute respiratory diseases and exacerbation of chronic ones. In order to study the prevalence of community-acquired pneumonia, the etiologic role of S. pneumoniaе and effectiveness of vaccination among children under the age of 6 in the town of industrial cities, we conducted a non-interventional epidemiologic study of serotypes of circulating pneumococci and their compliance with the declared composition of vaccines recommended for prevention of pneumococcal infection in children. We also studied incidence rates of community-acquired pneumonias among children under the age of five vaccinated against pneumococcal infection, depending on the schedule and beginning of immunization. Our findings indicate a significant role of pneumococcus in the etiology of community-acquired pneumonias among children under the age of 17 (24.14%).The established spectrum of serotypes of pneumococcus from nasopharyngial swabs in children under the age of 17 with community-acquired pneumonia in the town of this city showed that such serotypes as 19F, 14, 9V/A, 15A/F, 6A/B/C, 3, and 23F contributed the most to the development of pneumonia (79.97%). Pneumococcus serotypes found corresponded to the composition of PCV13 in 76.36% of cases and to that of PCV10 – in 67.27%. Proven the effectiveness of the vaccine, the rate of epidemiologic effectiveness was 48.7% in relation to pneumonia of any etiology. Shown the largest epidemiological effectiveness (54.8%) of vaccination in children vaccinated in an early period (under the age of 1).